Effectiveness between Salam Leaf Booking Water and Red Ginger Towards Reducing Acid Levels in Patients of Gout Arthritis - Hartono; Darmaningrum , Chicilia Puspita (Basic and Applied Nursing Research Journal, 2021)
Background. The prevalence of Gout Arthritis in the world is 34.2%. Gout Arthritis is characterized by an increase in uric acid levels >7.2 mg/dl in men and >6 mg/dl in women. This disease can be treated pharmacologically and non-pharmacologically, one of which is bay leaf and red ginger. Research purposes. The purpose of this study was to determine the effectiveness of boiled water of bay leaves and red ginger on reducing uric acid levels in patients with gout arthritis. Methods. This research method is a pre-experimental static-group comparison design. The sampling technique used purposive sampling. A sample of 60 respondents was divided into two groups of 30 respondents each, group A intervention boiled bay leaf water for 7 days, group B intervention boiled red ginger water for 7 days. Both groups were observed uric acid levels before and after the procedure using the GCU tool. Result: The results of the paired t-test analysis of group A p = 0.000 and group B p = 0.005 p value <0.05 which means there is a difference between before and after intervention A and intervention B were given. The results of the Independent t-test analysis showed that there was a difference in uric acid levels. after intervention A and intervention B with p = 0.004. The results showed that boiled water of bay leaves was more effective than boiled water of red ginger in reducing uric acid levels. Conclusion. Boiled water of bay leaves is more effective than boiled water of red ginger in reducing uric acid levels in gout arthritis patients